The PACOVAR-trial: A phase I/II study of pazopanib (GW786034) and cyclophosphamide in patients with platinum-resistant recurrent, pre-treated ovarian cancer - Eichbaum, Michael H. R.; Mayer, Christine; Eickhoff, Regina; Bischofs, Esther; Gebauer, Gerhard; Fehm, Tanja; Lenz, Florian; Fricke, Hans-Christian; Solomayer, Erich; Fersis, Nikos; Schmidt, Marcus; Wallwiener, Markus; et al. (BMC cancer, 2011)
The prognosis of patients with recurrent, platinum-resistant epithelial ovarian cancer (EOC) is poor. There is no standard treatment available. Emerging evidence suggests a major role for antiangiogenic treatment modalities in EOC, in particular in combination with the metronomic application of low dose chemotherapy. The novel, investigational oral antiangiogenic agent pazopanib targeting vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR) and c-kit is currently being studied in different tumour types and is already used as first line therapy in recurrent renal cell carcinoma. A combined therapy consisting of pazopanib and metronomic oral cyclophosphamide may offer a well-tolerable treatment option to patients with recurrent, pretreated EOC.